Computer Sales Administration Process - Linda (International Publisher, 2022)
The purpose of this study was to determine the computer sales administration process, to find out the constraints faced during the computer sales administration process, to find solutions to the problems encountered during the computer sales administration process. The research methodology used is descriptive qualitative which aims to describe the conditions and analyze the computer sales administration process. In this study, data related to the author's study are sourced from library studies, field studies, and documentation techniques. The results of research regarding the administrative process of computer sales, the authors draw the following conclusions: the computer sales administration process is very important, because it is very helpful and facilitates sales activities and other company activities. The obstacles faced in the administrative process of computer sales are that consumers who pay using a credit card will be charged an additional fee of 3% of the amount to be paid, when receiving goods from the warehouse to the outlet, there is often a miscommunication between the administration and warehouse staff so that it occurs. the difference between the goods or the goods sent are not in accordance with the travel documents, the lack of stock of goods makes it difficult to sell goods. The solution to the constraints faced in the administrative process of computer sales, namely: consumers who make payments using credit cards often refuse to pay an additional 3% fee, it is hoped that the company will make it easier to pay using credit cards such as working with the bank and providing promos 0% installments to credit card users, at the time of delivery of goods, warehouse staff are expected to re-check the email from the administration of what goods are needed by the outlet and recheck the quantity of goods and travel documents whether the goods sent are in accordance with the travel documents so that it will facilitate the delivery process goods, the administrative staff is expected to stock goods once a week to evaluate and update the stock of goods to make it easier at the time of sale.